2023
DOI: 10.1590/fst.100422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slice thickness and hot-air temperature on the kinetics of hot-air drying of Crabapple slices

Abstract: This study was investigated the effects of hot-air temperature and slice thickness on drying characteristics of Crabapple slices. Drying experiments were carried out in the ranges of 60-90 °C. The thickness conditions of Crabapple slices for thin layer drying were 3mm and 5mm. The increase in the temperature of the hot-air and the decrease in the thickness of the slicing causes the drying time to be significantly shortened. Fick's diffusion model was applied to describe the water transfer of the Crabapple slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
3
5
0
Order By: Relevance
“…This was attributed to the increasing energy of water molecules as the temperature increased, and water molecules evaporated from the sample more rapidly. The findings demonstrated that drying time decreased with increasing drying temperature which corroborate with previous studies [30,38].…”
Section: Sorption Model Mathematical Equation Referencessupporting
confidence: 91%
“…This was attributed to the increasing energy of water molecules as the temperature increased, and water molecules evaporated from the sample more rapidly. The findings demonstrated that drying time decreased with increasing drying temperature which corroborate with previous studies [30,38].…”
Section: Sorption Model Mathematical Equation Referencessupporting
confidence: 91%
“…The observed dissimilarities in results may be attributed to the composition structure, shape, and initial moisture content of the material, drying temperature, pretreatment, and drying equipment. Similar observations have been reported for drying crab (Jiang et al, 2023), piquin pepper(Ovando-Medina, 2023), and carrot (Wu et al, 2014).…”
Section: Effective Moisture Diffusion Coefficient (D Eff )supporting
confidence: 84%
“…A similar behavior was observed in the drying of other bean species (Junqueira et al, 2018;Maia et al, 2019;Quequeto et al, 2017). A higher partial pressure of water vapor in the product was observed at higher temperatures, which increased the drying speed, especially at the beginning of the process (Jiang et al, 2022;Siqueira et al, 2020a). The drying rate decreased over time, as the internal transfer of water mass in the form of steam to the periphery of the product was not compensated by the evaporation rate from the surface.…”
Section: Resultssupporting
confidence: 64%